DRAMATURGY IN THE IDENTITY AND IMAGE OF INFLUENCER MUSDALIFAH BASRI ON THE TIKTOK ACCOUNT @MUSDALIFAHBASRII - zahra, Amelia; Aesthetika, Nur Maghfirah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the application of front stage and back stage concepts in the formation of Musdalifah Basri's identity and analyze how her image shapes interactions with her followers on TikTok. Method: Using descriptive qualitative methods, data were collected through non-participatory observation on @musdalifahbasrii and @emde.team accounts, documentation, and literature studies. To analyze these objects, not all videos are sampled, but are specifically selected based on three main criteria. Results: The results of the study show that Musdalifah strategically uses his main account as a front stage to present a consistent comedic persona through hyperbolic appearances, styles, and settings. Uniquely, the back stage is deliberately exposed through his team account (@emde.team) to show a simple and collaborative work process, in order to build an authentic image and closeness to the audience. This dual strategy has proven to be successful in creating very high audience interaction, although it tends to be one-way. Novelty: The dual strategy of exposing both front stage and back stage through separate accounts to construct an authentic image and closeness to the audience, while maintaining a highly interactive but predominantly one-way engagement, highlights a unique approach in TikTok identity formation.